UPAYA PENINGKATAN LITERASI DI DESA LAMPEJI MELALUI MEDIA RUANG BACA - Achmad Saifur R; Arini Salsabila; Zida Rizqi A; Ihya Nurina R; Muhammad Fadlin T; Muhammad Khoiruddin; Galuh Adi Fransiska (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Reading activities are activities that need to be preserved and developed in Indonesia. According to research entitled "World's Most Literate Nations Ranked" conducted by Central Connecticut State University in 2016, Indonesia was ranked 60th out of 61 countries in terms of literacy levels. One of them is in East Java. Reading interest in Jember Regency has started to increase, reaching 54.7% compared to 47% during the Covid-19 pandemic. The reason the collaborative KKN team 67 moved in the realm of literacy was the fact during the DTKS survey activity, namely the large number of residents in Lampeji Village whose educational background only reached junior high school or high school, and what is even sadder is that this fact was also found in children of productive age. This is the basis for us to move in the realm of literacy as a form of prevention of bad possibilities happening to the next generation. Collaborative KKN students group 067 present a literacy corner which is placed in the Lampeji village hall in the Mumbulsari District area. One part of literacy that is the focus for development is reading culture. This research on the role of reading corners in fostering reading interest in the people of Lampeji Village uses qualitative methods. Reading Corners play a role in increasing the spirit of learning, providing readers with an understanding of science and facilitating the community to read books. Reading Corners in Lampeji Village act as an inspiring learning center, helping children and teenagers in Lampeji Village grow into a smart and knowledgeable generation.